Adaptive low‐priority transfer for high bandwidth and delay product networks. Issue 17 (7th October 2016) - Li, Xiaohui; Wang, Junfeng; Han, Li; Zhou, Yingjie; Han, Sunyoung
Abstract: As the exponential growth of the Internet, there is an increasing need to provide different types of services for numerous applications. Among these services, low‐priority data transfer across wide area network has attracted much attention and has been used in a number of applications, such as data backup and system updating. Although the design of low‐priority data transfer has been investigated adequately in low speed networks at transport layer, it becomes more challenging for the design of low‐priority data transfer with the adaptation to high bandwidth delay product networks than the previous ones. This paper proposes an adaptive low‐priority protocol to achieve high utilization and fair sharing of links in high bandwidth delay product networks, which is implemented at transport layer with an end‐to‐end approach. The designed protocol implements an adaptive congestion control mechanism to adjust the congestion window size by appropriate amount of spare bandwidth. The improved congestion mechanism is intent to make as much use of the available bandwidth without disturbing the regular transfer as possible. Experiments demonstrate that the adaptive low‐priority protocol achieve efficient and fair bandwidth utilization, and remain non‐intrusive to high priority traffic. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : It is demonstrated that ALP achieves performance improvements in terms of throughput and fairness over other low‐priority protocols. Specifically, ALP can always achieve higher throughput than other protocols in different network status, including different link bandwidths, packet loss rates, and router buffer sizes. ALP is able to achieve good fairness in homogeneous and heterogeneous OWD scenarios and be of low priority with standard TCP flows. Also, ALP is more efficient in terms of overall bandwidth utilization.